EPIDEMIOLOGI PSIKOSOSIAL DAN DETERMINAN SOSIAL PADA LAYANAN PRIMER: TINJAUAN LITERATUR DAMPAK KEAMANAN LAYANAN DAN EMPATI NAKES TERHADAP KEPUASAN MELALUI MEDIASI KEPERCAYAAN PASIEN DI PUSKESMAS KABUPATEN LOMBOK TENGAH NTB - Jaswadi Jaswadi (Jurnal Cakrawala Ilmiah, 2026)
Background: Primary health care at community health centers (Puskesmas) often focuses solely on technical-medical aspects, while psychosocial epidemiological factors are frequently overlooked. In Central Lombok Regency, the interaction between health providers and the community possesses unique socio-cultural dynamics that influence health outcomes. Objective: This study aims to analyze, through a literature review, the impact of service safety and health provider empathy on patient satisfaction, with patient trust as a mediating variable. Method: This study employs a Systematic Literature Review (SLR) method. Literature searches were conducted using Scopus and Google Scholar databases covering the years 2014-2024. The selection protocol used strict inclusion and exclusion criteria to obtain articles relevant to the primary care context and social determinants. Results: The synthesis of the literature shows that service safety and provider empathy are consistently primary predictors of patient satisfaction. It was found that patient trust plays a significant mediating role; service quality does not directly result in satisfaction without a foundation of trust. In the context of psychosocial epidemiology, trust acts as an emotional catalyst that strengthens the therapeutic relationship between providers and patients. Conclusion: Strengthening the empathetic capacity of health providers and the transparency of service safety is crucial for building community trust at the Puskesmas level to achieve sustainable service satisfaction